Determination of the Antagonistic Effects of Some Rhizospheric Bacteria against Macrophomina phaseolina under In Vitro Conditions - Özden Salman; Fatma Rana Bayram; Nuh Boyraz; Raziye Koçak (Turkish Journal of Agriculture: Food Science and Technology)
Macrophomina phaseolina (Tassi) Goid. is a fungal pathogen causes charcoal rot disease (Sin: Rhizoctonia bataticola) and is responsible for significant yield losses in many plants. In our study, we aimed to evaluate the antagonistic ability of 39 different bacteria, isolated from the fields of sugar beet in 2019, against the pathogen Macrophomina phaseolina isolated from sugar beet, beans and chickpeas. Approximately 31% of the bacteria showed antibiosis effect against the pathogen. It was determined that the effectiveness level of Lelliottia amnigena, Bacillus atrophaeus, B.pumilus and B. cereus (7 isolates) was moderate to high against Macrophomina phaseolina. Bacillus atrophaeus (PTo15-1a) showed the highest efficacy of 80%, 72.94% and 82.35% against Macrophomina phaseolina of chickpea, bean and sugar beet respectively. Lelliottia amnigena (Pto 14-1b) was moderately effective (57.78%) against the chickpea isolate of the pathogen. It was observed that of the seven Bacillus cereus isolates used in the experiment, three isolates (Pto14-1a, Pto12-1b, Pto17-1b) were highly effective against the chickpea pathogen, two (Pto12-1b, Pto14-2b) against bean pathogen, and one (Pto15-1b) against sugar beet isolate. Results have shown varied level of antagonism by different test bacterial against different Macrophomina phaseolina isolates, while the highest level of antibiosis shown by Bacillus atrophaeus against all pathogenic isolates indicated that it can be a potential future bioagent in managing the disease.